KRITIK FILSAFAT EKO-FEMINISME TERHADAP KONSEP KEPEMIMPINAN SUAMI DALAM KELUARGA - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Patriarchichal system practised in many societies confirm the concept of husband leadership in the family, including in the form of legal acts. Prob¬lem arises as that concept gives birth to the injustice conduct to women in pratriarchichal culture. This problem triggers the natal of feminist move¬ment including the eco-feminism fighting for justice for women. This thesis aims to study the criticism of eco-feminism against the concept of husband leadership in the family and the alternative leadership concept ecofeminism offers. Ecofeminism concerns about three main topics, i.e. the relationship pat¬tern between human being and God, human and human, also human and the nature. The fundamental principles in its methodology of reasoning are the unity, integrality, and harmony in wholeness. In studying the concept of husband leadership, the relevant topic is the relationship pattern between human and human, that when reflected critically will become the part of social philosophy study. Method used here is critical analysis involving the interpretation and critical evaluation of data. Due to its fundamental principles of reasoning, eco-feminism criticize the concept of husband leadership in the family, especially, in Indonesia. The weakness of the concept is its unability to create the harmonic relation¬ship pattern between husband and wife. The wife is always placed in subor¬dinate position that she is not free to express herself as a human being. Eco-feminism offers the concept of leadership that place feminin quality as the base of leadership. This alternative leadership concept highly value the democratic attitudes in the form of proportional power sharing between hus¬band and wife.